Rheological Behaviour of Chitosan-Starch Solution - Singh, Virpal; Kumari, Kamlesh (Asian Journal of Chemistry, 2013)
Blends of chitosan (Ch) and starch (St) in different proportions, considering chitosan as a main component were prepared. Rheological properties of blends such as viscosity and shear stress were investigated as a function of shear rate using Brookfield digital viscometer. The influence of shear rate and polymer concentration has been analyzed. The chitosan-starch solution showed a non-Newtonian flow behaviour. The solution properties such as density and refractive index were also measured.